Spectroscopic study of prompt-gamma emission for range verification in proton therapy - Kelleter, Laurent; Parodi, Katia; Tessonnier, Thomas (Physica medica, 2017)
We present the results of an investigation of the prompt-gamma emission from an interaction of a proton beam with phantom materials. Measurements were conducted with a novel setup allowing the precise selection of the investigated depth in the phantom, featuring three different materials composed of carbon, oxygen and hydrogen. We studied two beam energies of 70.54 and 130.87MeV and two detection angles: 90° and 120°. The results are presented in form of profiles of the prompt-gamma yield as a function of depth. In the analysis we focused on the transitions with the largest cross sections: 12C4.44→g.s. and 16O6.13→g.s.. We compare the profiles obtained under various irradiation conditions, with emphasis on the shape of the distal fall-off. The results are also compared to calculations including different cross-section models. They are in agreement with the model exploiting published cross-section data, but the comparison with the Talys model shows discrepancies.